Nursing History of Turkish Cypriots - Ufuk Kaya; Kerem Yıldız (Galenos Publishing House, 2021)
In terms of the historical development of nursing and education for Turkish Cypriots, articles in the literature are quite limited. The Cypriots initially stayed away from the nursing profession. In this period, the profession was carried out by nurses (sisters) who came to Cyprus from England. However, in time, the Cypriots also started to adopt the nursing profession. The first breakthrough in the field of nursing was the British government's sending a Turkish Cypriot (Türkan Aziz) and two Greek women to a nursing school in Beirut for a three-year education in 1935. After these years, the nursing profession and education were adversely affected after the attacks that started in 1963 but did not stop. Vocational School of Nursing was established in 1994 and has trained nurses for many years. Following this, nursing undergraduate, master and doctoral education have been started to be given in many universities in Northern Cyprus.